Big Five Personality Traits and Metaphor Construction: A Correlational Study on English Literature Students - Halim, Abd; Nasta, Mardiyanah; Halim, Nur Mutmainnna (ELLITE: Journal of English Language, Literature, and Teaching, 2025)
Metaphor is one of the essential elements of language that reflects a person’s level of creativity and capacity for abstract thinking. This study aims to identify the relationship between students’ personalities—based on the Big Five Personality model—and their ability to construct metaphors in English, using the theoretical framework of Lakoff & Johnson (1980). Employing a quantitative correlational approach, the research involved 65 active students from the English Literature Program at Universitas Negeri Makassar, selected through stratified random sampling. The instruments used were the Indonesian-adapted version of the Big Five Personality questionnaire (IPIP) and a metaphor writing test consisting of 20 items. Pearson correlation analysis revealed that the dimension Openness to Experience had a strong and significant positive relationship with metaphor construction ability, establishing it as the strongest predictor. Conscientiousness also showed a significant positive correlation, while Neuroticism had a significant negative correlation. In contrast, Extraversion and Agreeableness were not significantly associated with metaphor ability. These findings highlight that certain personality aspects—particularly openness to experience and self-discipline—play an important role in supporting students’ linguistic creativity, especially in metaphorical expression.